IMPLEMENTATION OF THE 7 HABITS OF GREAT INDONESIAN CHILDREN (7KAIH) MOVEMENT IN BOARDING SCHOOLS - Aan Khoirul Abidin; Karwanto Karwanto; Ima Widiyanah (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aimed to analyze the implementation of the Seven Habits of Great Indonesian Children (7KAIH) Movement in boarding-based junior high schools, focusing on SMP Al Anwari and SMP Kader Adz Dzikra Banyuwangi. A qualitative approach with a multisite case study design was employed to understand the implementation process, management patterns, and factors influencing the success of the program at each site. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and cross-site conclusion drawing. The findings showed that the implementation of 7KAIH in both schools was relatively effective, but with different strengths. SMP Al Anwari was stronger in integrating the program into boarding activities, developing operational work plans, controlling evening study time, and conducting regular evaluations. Meanwhile, SMP Kader Adz Dzikra was stronger in formal monitoring, human resource support, boarding facilities, nutrition management, and a wider range of social and sports activities. The habits most successfully developed in both sites were congregational prayer, learning activities, and social engagement, while waking up early and going to bed early remained the main challenges. These findings indicate that the success of 7KAIH implementation in boarding-based schools is strongly determined by policy integration, role modeling, organization, and consistent supervision. Keywords: 7KAIH; character education; boarding school; policy implementation; Multisite case study. Abstrak Studi ini menelaah implementasi program 7 Kebiasaan Anak Indonesia Hebat (7KAIH) di sekolah menengah pertama berbasis asrama, dengan fokus pada SMP Al Anwari Banyuwangi dan SMP Kader Adz Dzikra Banyuwangi. Dengan pendekatan kualitatif dan desain studi kasus multisitus, penelitian ini mengeksplorasi bagaimana program tersebut direncanakan, dilaksanakan, diorganisasi, diawasi, dievaluasi, serta dialami di kedua institusi. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan diskusi kelompok terarah, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan lintas situs. Temuan menunjukkan bahwa implementasi 7KAIH di kedua sekolah umumnya efektif, namun masing-masing memiliki kekuatan yang berbeda. SMP Al Anwari lebih unggul dalam mengintegrasikan program ke dalam rutinitas asrama, menyiapkan rencana kerja operasional, mengontrol belajar malam, serta melakukan evaluasi rutin. SMP Kader Adz Dzikra lebih kuat dalam pemantauan terstruktur, dukungan sumber daya manusia, fasilitas asrama, manajemen gizi, serta variasi kegiatan sosial dan olahraga. Kebiasaan yang paling berhasil dibangun di kedua sekolah adalah ibadah berjamaah, kebiasaan belajar, dan partisipasi sosial, sementara bangun pagi dan tidur lebih awal tetap menjadi tantangan utama. Temuan ini menyarankan bahwa efektivitas implementasi 7KAIH di sekolah berasrama bergantung pada integrasi kebijakan, keteladanan, pengorganisasian, dan pengawasan yang konsisten. Keywords: 7KAIH, pendidikan karakter, sekolah berasrama, implementasi kebijakan, studi kasus multisitus